Per‐unit transformation for the combined analysis of multi‐energy integration - Zhang Zhang; Fei Wang; Hui Fan (IET Renewable Power Generation)
Abstract To handle numerical issues caused by dimensional differences among heterogeneous states in integrated energy systems (IES), this paper proposes a novel per‐unit transformation method and explores its applications to the partial differential equation‐governed models. Initially, a unified IES model is developed, which encompasses both fast and slow dynamics in a generalized form. Subsequently, the per‐unit transformation is consistently applied to the fast and slow dynamics of the IES within the unified model framework. The proposed method's theoretical proofs demonstrate its ability to preserve structure and reduce complexity. Simulation results in various cases validate the accuracy of the per‐unit model and verify the effectiveness of the transformation in reducing conditional numbers. This reduction is particularly significant for improving efficiency in the combined analysis of the IES.